Pengaruh Capital Structure, Likuiditas, Profitabilitas, dan Firms Size terhadap Earnings Quality - Dewi, Siska (Department of Accounting, Faculty of Economics & Business, 2024)
The purpose of this study is to prove how the effect of capital structure, liquidity, profitability and company size on earnings quality. This study uses an analytical method, namely multiple linear regression with a quantitative approach. The samples in this study were 14 property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period from a total population of 86 companies. The results of this study prove that capital structure and profitability partially have a significant negative effect on earnings quality, liquidity partially has no effect on earnings quality, company size partially has a significant positive effect on earnings quality. Capital structure, liquidity, profitability and company size simultaneously affect earnings quality. In accordance with the results of this study, investors should pay more attention to the capital structure, profitability and company size of a company because these three things can affect earnings quality.